Досвід Маріупольського металургійного комбінату ім. Ілліча щодо освоєння борвміщуючих конструкційних сталей - Назюта, Л.Ю.; Тихонюк, Л.С.; Хавалиць, Ю.В.; Цюцюра, А.В.; Ісланкіна, О.Г. (Physico-technological Institute of Metals and Alloys, 2023)
Microalloying of steel with boron in the conditions of Mariupol Metallurgical Plant named of Ilyich in a period of unstable economic condition of Ukraine is especially important, because it is focused on the domestic market of structural metal, and also improves the quality of export products. In Ukraine, the production of boron-containing steels is concentrated at the enterprises of Metinvest LLC and does not exceed 2 % of the total output. At the same time, Ukrainian enterprises import such steels and, especially, structural ones for construction and agricultural engineering. Therefore, an increase in the production and assortment of boron-containing steel is aimed at improving the quality and expanding the market for finished products. Microalloying with boron of structural steels of ordinary range is extremely rarely used due to the stereotype of opinions about the mechanism of the effect of boron on the quality indicators of the metal. In the work, the optimal mode of out-of-furnace processing is determined in order to stabilize the quality indicators of the finished metal. The analysis of the degree of assimilation of the main ferroalloys and the quality of the finished product is carried out according to the statistical processing of the melts of the current production. It is shown, that in the smelting of medium-carbon steels for general purposes, microalloying with boron in the conditions of the Mariupol Metallurgical Plant named of Ilyich does not guarantee an increase in the quality indicators of the metal, however, it stabilizes their properties and allows, other things being equal, to reduce aluminum consumption by 8–10 %. In the smelting of 30MnB5 steel due to microalloying with boron, a reduction in the consumption of the main deoxidizers (manganese and aluminum by 0.12 kg/t of steel each) was achieved. The microalloying technology of low-carbon steel (08пс) is currently being specified. It was recommended to Ukrainian metallurgists to increase production volumes of ordinary (mass) boron-containing steels of structural assortment.